2003
DOI: 10.1097/00005537-200301000-00029
|View full text |Cite
|
Sign up to set email alerts
|

Esthesioneuroblastoma: The Northwestern University Experience

Abstract: Esthesioneuroblastoma is a rare tumor that is potentially curable by surgical resection and radiation therapy. However, the rate of local failure is high, and late recurrences are not uncommon. The role of chemotherapy warrants further investigation.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
49
1
2

Year Published

2004
2004
2017
2017

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 72 publications
(54 citation statements)
references
References 29 publications
2
49
1
2
Order By: Relevance
“…The main reported symptoms in our series were nasal block and headache; contrary to other papers, [11][12][13] epistaxis was infrequent. The differential diagnosis is made with other nasosinusal tumors, such as the inverted papilloma and squamous cell carcinomas.…”
Section: Discussioncontrasting
confidence: 97%
See 2 more Smart Citations
“…The main reported symptoms in our series were nasal block and headache; contrary to other papers, [11][12][13] epistaxis was infrequent. The differential diagnosis is made with other nasosinusal tumors, such as the inverted papilloma and squamous cell carcinomas.…”
Section: Discussioncontrasting
confidence: 97%
“…7,18 Preoperative CT and MRI are essential for surgical planning. [11][12] Minor complications such as cerebrospinal fluid leaks and intraorbitary hemorrhage have been described in this technique; the risk is similar to that of endoscopy in chronic sinusitis. 7 Several authors still defend en bloc craniofacial resection as the treatment of choice for tumors in general.…”
Section: Discussionmentioning
confidence: 97%
See 1 more Smart Citation
“…They occur at various ages, but have bimodal peaks in the second/third and sixth/seventh decades of life [5], and their rarity and highly heterogeneous nature have led to divergent opinions concerning their origin, growth, diagnosis, and management [1,2,6].…”
Section: Introductionmentioning
confidence: 99%
“…To improve the outcome, chemotherapy has been used in neoadjuvant and adjuvant treatments of locally advanced tumors; however, the survival data reflecting the outcome of chemotherapy are variable and chemotherapy's additional benefit, compared to just undergoing surgery or radiotherapy alone, remains uncertain [12,[33][34][35] . In a study reported by a group from the University of Virginia, patients with Kadish stage C received preoperative sequential chemotherapy (two cycles of vincristine + cyclophosphamide ± doxorubicin) and radiation therapy, followed by craniofacial resection.…”
Section: Discussionmentioning
confidence: 99%